Overcast-Oriented Technologies as a New Method of Interaction of Cultures in the Field of Higher Musical- Pedagogical Education - Tokhta Ametovna Yuldasheva (Zien Journals, 2023)
The article considers the modern information resources and technology as a possible method of interaction in the framework of the "dialogue of cultures" in the musical-educational process. Author discusses the main cloudy-focused technologies that are of interest to the teacher-musician at the University, it is made an overview; the analysis of the most promising services in the work of the teacher-musician is done, the examples of their application in practice are given
Keywords: the dialogue of cultures, cloudy-oriented learning technologies, teacher, musician, lecturer, mobile educational technology, professional musical education, Google services